Bank Syariah dan Hubungannya Dengan Lembaga Keuangan dan Bisnis Lainnya Di Indonesia - Yuliana Yuliana; Nurnasrina Nurnasrina; Heri Sunandar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This paper discusses Islamic banking and its relationship with financial institutions and other businesses in Indonesia. Banks and financial institutions have a role as a Financial Intermediaries whose function is to collect funds from the public and channel them back to those who need funds. The main activity of Islamic banks is to provide financing to customers, where these activities are related to other financial institutions. This research is library research (Library Research) with a thematic method. The results of this discussion state that Islamic banks, financial institutions, and other businesses have a close relationship, where they need each other in carrying out their operations.Keywords: Islamic Banks, Financial Institutions, Business